Un RER à Bruxelles ? Socio-histoire des rivalités et des régulations politiques (1989‑2013) - Ludivine Damay (Brussels Studies)
This article traces the history of the project for a Regional Express Railway (RER) from, towards, in and around Brussels by highlighting the major conflicts between the different stakeholders which have underlain the issue from the start. The RER is at the heart of rivalries regarding the uses, users and visions of the city to be favoured, as well as the concrete mobility policies to develop and the role of the Société Nationale des Chemins de fer Belges (SNCB) in this respect. The article also traces the different steps in the political regulation of the issue, covering the phases of progress and standstill which mark out the history of the RER. By shedding light on the history of these rivalries and antagonisms which have never lost their substance, this article provides a better view of the current situation, illustrating the power of misunderstandings.